Analisis Kinerja Keuangan Pada Sub Sektor Pakan Ternak Yang Terdaftar Di Bursa Efek Indonesia - Apriyanti, Indri Rama (IJAcc, 2025)
This study aims to analyze financial performance based on current ratio, quick ratio, debt to asset ratio, debt to equity ratio, return on asset and return on equity in animal feed companies listed on the IDX in 2019-2023. The method used in this study uses a quantitative method with secondary data and the determination of the sample in this study is purposive sampling with certain criteria, so that the number of samples obtained is 9 companies. The conclusion drawn from the results of this study is that the average indicators of current ratio, quick ratio, debt to equity ratio, return on asset and return on equity are still far below industry standards, only debt to asset ratio meets industry standards. Keywords: Current Ratio, Quick Ratio, Debt To Asset Ratio, Debt To Equity Ratio, Return On Asset dan Return On Equity.